The life cycle of Bucephalus margaritae Ozaki & Ishibashi, 1934 (Digenea, Bucephalidae) from the coast of Santa Catarina State, Brazil - DOI: 10.4025/actascibiolsci.v32i1.5596 - Natalia da Costa Marchiori; Aimê Rachel Magenta Magalhães; Joaber Pereira Junior (Acta Scientiarum. Biological Sciences, 2009)
The orange disease is considered the main parasitosis in Perna perna mussel. It is caused by a complex life cycle bucephalid, involving three hosts, among them mollusks and fishes. With the aim of contributing to the knowledge of orange disease in mussel culture, the parasite life cycle was investigated. Experimental studies and monthly samples in the study area allowed the identification and characterization of the Bucephalus margaritae life cycle. Larvae and adults of B. margaritae were fixed in 5% formaldehyde, stained with Gomori’s trichrome, clarified in creosote and mounted in Canada balsam. The cercariae are found in the first intermediate host P. perna inside the sporocysts, which have the form of orange and ramified filaments. The metacercariae encysts in the gills and gill cavity of the second intermediate host, the blenniid Hypleurochilus fissicornis. The definitive host Menticirrhus americanus is infected ingesting blenniids parasitized with metacercariae. The high parasitological indexes of B. margaritae suggests that M. americanus and H. fissicornis act as the main definitive and intermediate hosts, respectively, in the trematode life cycle. The blenniid H. fissicornis is a new intermediate host to the species.